ولایت نکاح سے متعلق پاکستان کی اعلی عدالتوں کے فیصلے : شریعت اسلامیہ کی روشنی میں تجزیاتی مطالعہ: Decisions of Pakistan's Apex Courts on Wilayāh al-Nikāh: An Analytical Study in the Light of Islamic Law (Al-Qamar, 2020)
Since the four school of thoughts came into existence, a little bit conflict appeared between their thinking on the basis of arguments due to follow one particular “Imam’’ of the Muslims are all over the world facing problem due to opinion they adopted in the books of fiqh. Three of them agreed on the point that no marriage is allowed without consent of father of a girl but Imam Abu Hanifa is on the other side has opposite opinion that the girl consent must be considered. This is the main facts between Judgement in different way. In this article Islamic point of views and the court decisions have been presented as comparative deep study of Islamic law. A number of fruitful conclusions can be derived from this research to save ourselves from negative differences and conflicts. When somebody report something or matters about others, we should investigate first then we should take action. Natural type of difference in opinions are unavoidable phenomenon so it should be on the basis of authentic proves and positivity. Differences between Imam are not personal but they are all have arguments, knowledge of Quran and Sunnah and proves. This article will open new ways to understand the marriage with or without consent of Wali and the various arguments.
Keywords: Marriage; Courts; Nikah; Wali; Shariah; Consent